LEGAL EDUCATION ON THE DEVELOPMENT OF INFORMATION TECHNOLOGY AND THE IMPLICATIONS OF SOCIAL MEDIA ABUSE FOR YOUNG GENERATION - Khomaini, Khomaini (Universitas Negeri Medan, 2024)
The development of information technology has had a significant impact on daily life, especially for the younger generation. This research aims to explore effective legal education methods in dealing with developments in information technology and the impact of social media abuse on the younger generation. Research methods involve surveys, interviews, and documentation analysis. The survey was conducted among the students in Taman Siswa school to identify their understanding of laws related to information technology and social media. Interviews were conducted with legal experts and educators to identify effective educational methods. Document analysis involves searching for relevant laws and regulations. The research results show that most of the younger generation have a limited understanding of the laws related to information technology and social media. Effective educational methods involve the use of case studies, simulations, and interactive discussions. As a result, the younger generation who take part in this educational program are better able to understand the legal implications of using information technology and social media. In addition, the government and educational institutions need to improve legal education and integrate it into the educational curriculum to provide better knowledge of laws related to information technology to the younger generation. Increasing understanding of the law can help the younger generation make wiser decisions in the use of information technology and social media, and reduce the risk of breaking the law.